Recent advances in computational design of potent aromatase inhibitors: open-eye on endocrine-resistant breast cancers. (3rd October 2019) - Spinello, Angelo; Ritacco, Ida; Magistrato, Alessandra
ABSTRACT: Introduction : The vast majority of breast cancers (BC) are estrogen receptor positive (ER+). The most effective treatments to fight this BC type rely on estrogen deprivation therapy, by inhibiting the aromatase enzyme, which performs estrogen biosynthesis, or on blocking the estrogens signaling path via modulating/degrading the estrogen's specific nuclear receptor (estrogen receptor-α, ERα). While being effective at early disease stage, patients treated with aromatase inhibitors (AIs) may acquire resistance and often relapse after prolonged therapies. Areas covered : In this compendium, after an overview of the historical development of the AIs currently in clinical use, and of the computational tools which were used to identify them, the authors focus on current advances in obtaining innovative inhibitors via molecular simulations. These inhibitors may help prevent or delay relapse to AIs. Expert opinion : BC remains the most diagnosed and the leading cause of death in women. In spite of the success of the adjuvant endocrine therapy, which has enormously prolonged woman's survival rate, the increasing emergence of the resistance phenomena calls for the development of novel approaches and drugs to fight it. The discovery of the last generation of AIs dates back to two decades ago, underlying a paucity of research efforts.